2023
DOI: 10.3389/fpsyt.2022.947622
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain activity and functional connectivity after MDMA-assisted therapy for post-traumatic stress disorder

Abstract: Introduction3,4-methylenedioxymethamphetamine-assisted therapy (MDMA-AT) for post-traumatic stress disorder (PTSD) has demonstrated promise in multiple clinical trials. MDMA is hypothesized to facilitate the therapeutic process, in part, by decreasing fear response during fear memory processing while increasing extinction learning. The acute administration of MDMA in healthy controls modifies recruitment of brain regions involved in the hyperactive fear response in PTSD such as the amygdala, hippocampus, and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 112 publications
0
6
0
1
Order By: Relevance
“…In addition, the interpretation of the findings mentioned above are limited by the heterogeneous research methods used, including the types of tasks, as well as the way drugs were administered (e.g., intranasal versus oral administration). Other recent studies using ketamine 59, 60 or psychedelics 61 were not included as they did not compared patients with PTSD to groups of TEC or HCs. An important limitation is the exclusion of studies of PTSD patients showing severe comorbid disorders; although this would represent a more ecological group, it could also hinder the effects of the studied pharmacological agents on brain function solely associated with PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the interpretation of the findings mentioned above are limited by the heterogeneous research methods used, including the types of tasks, as well as the way drugs were administered (e.g., intranasal versus oral administration). Other recent studies using ketamine 59, 60 or psychedelics 61 were not included as they did not compared patients with PTSD to groups of TEC or HCs. An important limitation is the exclusion of studies of PTSD patients showing severe comorbid disorders; although this would represent a more ecological group, it could also hinder the effects of the studied pharmacological agents on brain function solely associated with PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies using ketamine 59,60 or psychedelics 61 were not included as they did not compared patients with PTSD to groups of TEC or HCs. An important limitation is the exclusion of studies of PTSD patients showing severe comorbid disorders; although this would represent a more ecological group, it could also hinder the effects of the studied pharmacological agents on brain function solely associated with PTSD.…”
Section: Limitationsmentioning
confidence: 99%
“…34 Meanwhile, neuroimaging studies on humans have discovered that MDMA decreases cerebral blood flow, a measure of brain activity, in the amygdala. 35 In addition, MDMA elevates functional connectivity between the amygdala and hippocampus 35,36 (note that the second study only found a trend-level effect), a region that supports the encoding and retrieval of memories. 37 Taken together, these findings from both humans and rodents seem to be consistent with the clinical observation that MDMA-assisted therapy facilitates access to traumatic memories that were previously repressed.…”
Section: Chemistry and Mechanism Of Actionmentioning
confidence: 95%
“…Zudem wird davon ausgegangen, dass MDMA durch die Erhöhung der Konnektivität zwischen Amygdala und Hippocampus die Aufarbeitung traumatischer Erinnerungen im Rahmen des therapeutischen Prozesses begünstigen kann [7]. Eine fMRT-Studie konnte nach einer MDMA-gestützten Therapie eine Veränderung in Gehirnregionen nachweisen, welche mit Angst, PTBS und autobiografischen Gedächtnisprozessen assoziiert sind [8]. Zusätzlich sollte erwähnt werden, dass alle klinische Studien mit dem MDMA-Razemat durchgeführt worden sind.…”
Section: Neurobiologieunclassified